Four Bosons Electromagnetism (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Based on light invariance and electric conservation a four bosons electromagnetism is proposed. It enlarges theelectric charge conservation beyond displacement current and Dirac charge to a new physical situation where the electromagnetic phenomena is mediated by the usual photon plus a massive photon and two additional charged vector bosons. Considering the enlarged abelian gauge symmetry U (1)? SO (2) transforming under a same gauge parameter a non-linear electro magnetism involving four bosons is introduced. It deploys a Lagrangian containing massless, massive and charged fields with three and four vector bosons interactions. The corresponding Noether’s relations and classical equations of motion are studied. They provide a whole dynamics involving granular, collective terms through antisymmetric and symmetric sectors. It develops a new photon equation which extends the Maxwell’s one. Self interacting photons are obtained. A four boson electromagnetic flux is derived. It expresses an electromagnetism transfering ?Q = 0 and | ?Q |= 1, not more limited to just a massless photon. There is a new electromagnetic flowing to be understood, where aside of electric charge conservation, it appears a neutral electromagnetism. There are six neutral electromagnetic charges beyond electric charge as consequences from non-linearity. Two are derived from the second Noether identity and four from variational continuity equations. An electromagnetic flux being conducted by a whole physics is generated. Based on fields set, it develops a determinism under the meaning of directive and circumstance. Interpreting that, light invariance concises the photon as directive, the photon becomes a whole maker. It assumes the symmetry command which will control the conservations laws and opportunities. Consequently, one combines the symmetry equation derived from Noether theorem with the four equations derived from variational principle, and an effective photon equation is obtained. A kind of Navier-Stokes electromagnetic flow is derived. It yields a four bosons electromagnetism preserving electric charge conservation plus introducting the meaning of chance through symmetry management.